Together We can Figure It out: Groups Find Hospitality Robots Easier to Use and Interact With Them More than Individuals - Preusse, Harrison; Skulsky, Rebecca; Fraune, Marlena R.; Stringam, Betsy Bender (Frontiers in Robotics and AI, 2021)
As robots are becoming more prevalent and entering hospitality settings, understanding how different configurations of individuals and groups interact with them becomes increasingly important for catering to various people. This is especially important because group dynamics can affect people’s perceptions of situations and behavior in them. We present research examining how individuals and groups interact with and accept a humanoid robot greeter at a real-world café (Study 1) and in an online study (Study 2). In each study, we separately examine interactions of individuals, groups that participants formed after they arrived at the café (new-formed groups), and groups that participants arrived with at the café (pre-formed groups). Results support prior findings that groups are more likely to interact with a public robot than individuals (Study 1). We also report novel findings that new-formed groups interacted more with the robot than pre-formed groups (Study 1). We link this with groups perceiving the robot as more positive and easy to use (Study 2). Future research should examine perceptions of the robot immediately after interaction and in different hospitality contexts.